Insight Into the Anti-staphylococcal Activity of JBC 1847 at Sub-Inhibitory Concentration - Ronco, Troels; Kappel, Line H.; Aragao, Maria F.; Biagi, Niccolo; Svenningsen, Søren; Christensen, Jørn B.; Permin, Anders; Saaby, Lasse; Holmstrøm, Kim; Klitgaard, Janne K.; Sabat, Artur J.; Akkerboom, Viktoria; et al. (Frontiers in Microbiology, 2022)
Multi-drug resistant pathogens constitute a serious global issue and therefore, novel antimicrobials with new modes of action (MOA) are urgently needed. Here, we investigated the MOA of a phenothiazine derivative (JBC 1847) with high antimicrobial activity in Staphylococcus aureus, using a wide range of in vitro assays, flow cytometry and RNA transcriptomics. The flow cytometry results showed that JBC 1847 rapidly caused depolarization of the cell membrane, while a macromolecule synthesis inhibition assay showed that the synthesis rates of DNA, RNA, cell-wall and proteins, respectively, were strongly decreased. Transcriptome analysis of S. aureus exposed to sub-inhibitory concentrations of JBC 1847 identified a total of 78 down-regulated genes, whereas not a single gene was found to be significantly up-regulated. Most importantly there were down-regulation of genes involved in ATP-dependent pathways, including histidine biosynthesis, which is likely to correlate with the observed lower level of intracellular ATP-level in JBC 1847 treated cells. Furthermore, we showed that JBC 1847 is bactericidal against both exponential growing cells and cells in a stationary growth phase. In conclusion, our results showed that the antimicrobial properties of JBC 1847 were primarily caused by depolarization of the cell membrane resulting in dissipation of the proton motive (PMF), whereby many essential bacterial processes are affected. JBC 1847 resulted in lowered intracellular levels of ATP followed by decreased macromolecule synthesis and down-regulation of genes essential for the amino acid metabolism in S. aureus. Bacterial compensatory mechanisms for this proposed multi-target activity of JBC 1847 seem to be limited based on the observed very low frequency of resistance towards the compound.